Utu: Finding a Balance for the Legal Māori Dictionary - Ahu, Tai; Hoare, Rachael; Stephens, Māmari (Victoria University of Wellington Law Review, 2011)
This article describes the authors' experience of attempting to confine the word utu to a list of distinct, Western legal glosses. The article highlights the complexity involved in drafting a comprehensive legal dictionary entry for utu that achieves an appropriate balance between the traditional customary meanings and Western legal meanings.